2001
DOI: 10.1007/s001980170013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Disease Activity and Serum Levels of Vitamin D Metabolites and Parathyroid Hormone in Ankylosing Spondylitis

Abstract: Vertebral fractures due to osteoporosis are a common but frequently unrecognized complication of ankylosing spondylitis (AS) and various factors may contribute to the development of osteoporosis in AS. It is known that inflammatory activity in rheumatic disease (i.e., proinflammatory cytokines) itself plays a possible role in the pathophysiology of bone loss. 1,25-Dihydroxyvitamin D3 (1,25(OH)2D3) seems to be another possible candidate for mediatory function in regulating both the inflammatory process and bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 25 publications
(32 reference statements)
1
41
2
7
Order By: Relevance
“…Apart from a cross-sectional design the limitation of this study is the lack of data for bone turnover markers, parathyroide hormone or vitamin D3, which could have revealed a better insight of association between activity parameters of both osteoporosis and AS [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a cross-sectional design the limitation of this study is the lack of data for bone turnover markers, parathyroide hormone or vitamin D3, which could have revealed a better insight of association between activity parameters of both osteoporosis and AS [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the acute phase reactant ESR and CRP was significantly elevated and inversely correlated with vitamin D levels in AS patients [13], disease activity ASDAS was negatively correlated with BMD because of vitamin D receptor gene may contribute to BMD differences in patients with AS, as gene polymorphisms are also linked to inflammatory activity [18]. Thus, osteoporotic risk may be significantly increased with raised serum levels of bone turnover markers and low levels of vitamin D. Previous study also has shown that the relationship between vitamin D with CRP and ESR, were significantly negatively correlated [19]. In addition, axSpA patients femoral BMD T/Z-score was negatively correlated with ALP, spinal stiffness and BMI.…”
Section: Discussion:-mentioning
confidence: 93%
“…While several studies had shown the aggravating effect of vitamin D's deficiency in the activity markers of AS disease [61][62][63][64] , other studies have not found any correlation [65][66][67] . Although, there is evidence for increased risk of AS in people with deficiency of vitamin D [68][69][70] further studies are required to clarify the causal relationship between the deficiency of vitamin D and activity of AS disease.…”
Section: Vitamin D and Severity Of Asmentioning
confidence: 90%
“…Additionally, Hmamouchi et al in another study, with 653 axSpA patients, mentioned that 25(OH)D had a significant inverse correlation with AS disease activity score, using CRP and Bath Ankylosing Spondylitis Metrology Index (BASMI) 73 . In studies that examined the relationship of 1,25(OH) 2 D with disease activity markers, found a significant inverse correlation between 1,25(OH) 2 D and ESR, BASDAI and CRP 63,64 . In contrast, there are studies that indicated that there is no correlation between 25(OH)D and disease activity [74][75][76] .…”
Section: Therapeutic Effect Of Vitamin D Supplementation In Asmentioning
confidence: 99%
See 1 more Smart Citation